Applying Clinical Reasoning Theories to Kinesiology: Advancing the Education of Future Healthcare Professionals - Ataman, Rebecca; Ibey, Robyn J. (International journal of kinesiology in higher education, 2022)
In Canada, kinesiology academic units are undergoing change. The growth of kinesiology as a health profession is reflected in increased clinical course offerings to train student clinicians. These courses require clinical educators, however, not all programs have clinical staff and faculty with the required knowledge or experience. In particular, prospective clinical educators may lack fundamental knowledge of clinical reasoning theory. Clinical reasoning is defined as problem solving and judgment in relation to patient or client assessment, diagnosis, treatment and management, and is considered to be essential for the development of autonomous health professionals. Clinical reasoning theory is applied in an educational context to streamline and enhance student clinician development. Unlike in the education of other health professionals, there has been no literature detailing the application of clinical reasoning theory to the kinesiology educational context. Thus, the objectives of this paper are to: (1) introduce the theories in clinical reasoning relevant to kinesiology, (2) link these theories to practical educational strategies and, (3) connect these strategies directly to the teaching of clinical kinesiology subjects.